The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/en13081882
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Diversion Cavity Geometry on the Performance of Gas-Liquid Two-Phase Mixed Transport Pump

Abstract: For the purpose of improving the transport capability of the mixed transport pump, a new self-made three-stage deep-sea multiphase pump was taken as the research object. Based on the Euler-Euler heterogeneous flow model, liquid (water) and gas (air) are used as the mixed media to study the external characteristics and internal flow identities of the mixed pump under different gas volume fraction (GVF) conditions. According to the simulation results, a local optimal design scheme of the diversion cavity in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The Euler-Euler inhomogeneous hydrodynamic model was provided for numerical calculation, which considered not only velocity slip, but also momentum transfer and interphase force. According to the research of Li et al's [6,7], two turbulence models were used to solve different media, among which the SST k-ω model was selected for continuous phase, and the Discrete Phase Zero Equation model was selected for discrete phase.…”
Section: Governing Equationsmentioning
confidence: 99%
“…The Euler-Euler inhomogeneous hydrodynamic model was provided for numerical calculation, which considered not only velocity slip, but also momentum transfer and interphase force. According to the research of Li et al's [6,7], two turbulence models were used to solve different media, among which the SST k-ω model was selected for continuous phase, and the Discrete Phase Zero Equation model was selected for discrete phase.…”
Section: Governing Equationsmentioning
confidence: 99%
“…Experimental results show that, for the multiphase pump at the pressure difference of 0.4 MPa and 1.0 MPa, the flow rate decreased by 18.7% and 25.7% with an increase of the gas volume fraction from 20% to Processes 2021, 9, 1025 2 of 18 90%, respectively. Chenhao Li [11] based on the Euler-Euler model, used water and air as the mixed media to study the external characteristic and internal flow of the multiphase pump under different gas volume fractions. LI Chenhao [12] also found that the variation tendency of the pressurization capacity in the multiphase pump is uniform from the first stage to the last stage under the gas-liquid two-phase condition, and the pressurization capacity of the last stage is more variable with different gas volume fractions.…”
Section: Introductionmentioning
confidence: 99%
“…Liu M. et al [18] also proposed a hydraulic design approach of a controllable blade angle oriented with a multiphase pump based on an impeller and diffuser; the results revealed that the distributions of GVF as well as the pressure would be of more uniformity following the optimization, thus enhancing transporting performance of the pump. Li C. et al [19] carried out research on the outer features and inner flow identities of the multiphase pump amidst various GVF circumstances on the basis of the Euler-Euler heterogeneous flow model. The results offered showed that the head and efficiency presented obvious improvement when the reduction of the inner wall of the diversion cavity occurred to 4 mm to the radial direction.…”
Section: Introductionmentioning
confidence: 99%